DUdetector: A dual-granularity unsupervised model for network anomaly detection - Geng, Haijun; Ma, Qi; Chi, Haotian; Zhang, Zhi; Yang, Jing; Yin, Xia (Computer networks (Amsterdam, Netherlands : 1999), 2025)
Internet of Things (IoT) devices are often used as springboards for network intrusion due to the open nature of IoT protocol stacks that enable automatic inter-connection and data sharing among devices, so it is critical to develop network anomaly detection algorithms that can be deployed at important nodes such as gateways and routers. However, existing detection algorithms based on signature rules and supervised machine learning heavily rely on known anomaly types, yielding low detection accuracy when deployed in realistic network environments with a significant number of unknown attacks. With this in mind, we propose DUdetector, an unsupervised anomaly detection algorithm by employing Transformer and Conv1d&MaxPool1d AutoEncoder with residual connection (abbr., CM&RC-AE) to realize a dual-granularity learning from the perspective of segments and points, respectively. Specifically, we perform coarse-grained segment-level anomaly detection based on an improved Transformer to detect whether there is any anomalous traffic within a time window. Then, we perform fine-grained point-level anomaly detection based on CM&RC-AE for each packet within the problematic segment output by the first step. Extensive experiments on three datasets (SSDP Flood, Mirai and IDS2017) demonstrate that our DUdetector achieves a better performance than existing work: an F1-score of 95.98% for Mirai, and over 99.2% for both SSDP Flood and IDS2017, with false positive rates less than 0.5% for all three datasets.